PERLINDUNGAN ANAK OLEH MASYARAKAT DITINJAU DARI MAZHAB SEJARAH DI DALAM PENERAPAN PRINSIP THE BEST INTEREST OF THE CHILD PADA KEHIDUPAN ANAK DI INDONESIA - Laurensius Arliman (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
Child has the human rights protected by law, applicable even in the womb, because the children are also entitled to legal protection for all the activities that lead to growth and development in the future. History in the school of Law, also explained how the law provides real protection against children. Legal protection of children in Indonesia have applied the principle of the best interest of the child, but in fact the application of that principle remains unimplemented. In the journey Indonesian government has also issued rules relating to the protection of children as follows: Law No. 4 of 1979 on Child Welfare, Law No. 3 of 1997 on Juvenile Justice and Law No. 23 of 2002 on Child Protection. As a result of the development of child protection. then the government changed, renewed, ratified and issued new rules related to the protection of children, namely Law No. 9 of 2012 on the Ratification of the Optional Protocol To The Convention On The Child On The Involvement Of Children In Armed Conflict, Law Number 10 Year 2012 on Ratification of the Protocol To The Convention on The Rights Of The Child on The Sale Of Children, Child Prostitution's Child Pornography, Law No. 11 of 2012 on the Criminal Justice System Child and Act No. 35 of 2014 Amendment Act No. 23 of 2002 on Child Protection. But still, realize the protection of children still can not be implemented, due to lack of community participation and awareness in implementing children's rights.Keywords: Child, Society, History Sect, Protection, Indonesia